COST ECONOMICS OF BREWERY WASTE IN JERSEY CROSSBRED DAIRY CATTLE UNDER FARMERS’ FIELD CONDITIONS - B. Rajesh Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to assess the cost economics of brewery waste in twenty four Jersey crossbred dairy cattle for one year with three treatments viz., control (T0), brewery waste (T1) and balanced ration (T2) in farmer’s field conditions with eight animals in each group. The control, brewery and balanced ration animals were fed as per traditional and standard feeding practices. Statistical analysis revealed a significant (P<0.01) increase in the cost of concentrates (Rs. 15401.59/-) and total feed cost (Rs. 33278.93/-) for brewery waste fed dairy cattle than control animals. Also significant (P<0.05) increase in average gain of milk yield (0.73 Kgs /animal/day) was noticed for brewery waste fed animals than control. It is imperative to note that the total returns (Rs. 54653.18/-) were significantly (P<0.05) higher for brewery waste treated than control (Rs. 45393.15/-) animals. No significant (P>0.05) difference was evident in lactation days, cost and net returns per Kg of milk production using brewery waste. It can be concluded that farmers can utilize brewery waste to increase milk yield and total returns for augmenting income generation.